Myofibroblastoma of the Female Breast with Admixed but Distinct Foci of Spindle Cell Lipoma: A Case Report - Hazem A. H. Ibrahim; Sami Shousha (Hindawi Limited, 2013)
Mammary myofibroblastoma (MFB) is a rare benign spindle neoplasm that affects both sexes with a male predominance. It can exhibit a wide range of histological patterns. We report a case of epithelioid/spindle MFB of the female breast with admixed, but distinct, foci of spindle cell lipoma. Whilst all the spindle cells within the tumour expressed CD34, AR, ER, BCL2, and CD10, only those within the myofibroblastoma expressed desmin and only those within the lipomatous areas expressed S100. This finding, to our knowledge, is a novel one that has not been reported before.